A Novel Semiautomatic Technique for Volumetric Assessment of the Alveolar Bone Defect Using Cone Beam Computed Tomography. (May 2015) - Linderup, Bo Werner; Küseler, Annelise; Jensen, John; Cattaneo, Paolo M.
Objective: The aims of this study were (1) to determine the three-dimensional anatomical boundaries of the alveolar bone defect in cleft lip and palate (CLP) patients, (2) to precisely translate these anatomical boundaries into reliable cephalometric landmarks and planes that can be used for cone beam computed tomography (CBCT) analysis, (3) to standardize image acquisition and reconstruction parameters, and (4) to test the reproducibility of the proposed protocol for measuring the predefined alveolar bone defect, using a third-party software. Methods: The alveolar bone defect volume of 10 randomly selected patients with unilateral CLP (UCLP) aged 8 years and 6 months to 11 years and 2 months was evaluated on preoperative and 1-year postoperative CBCT scans using a semiautomatic, standardized protocol. The alveolar bone graft outcome was calculated as a percentage of the bone fill using the formula (VOLpre – VOLpost)/VOLpre) × 100. Intra- and interobserver reliability was assessed. Results: Intra- and interobserver reproducibility was excellent for volumes and bone fill as no statistically significant difference ( P < .001) was seen between the different sets of measurements, and Pearson correlation coefficients were large (intraobserver: r > .9849, interobserver: r > .8784). The Bland-Altman plots indicated that the differences between the plots were not patterned. Conclusions: Volume determination using CBCT, third-party medical image processing software, and the presently defined image acquisition and reconstruction parameters, including anatomical boundaries, is a reproducible and practical method for assessing the volumetric outcome of secondary alveolar bone grafting in patients with UCLP.